Pelatihan Peduli Sejiwa Dalam Optimalisasi Peran Duta UKS dan Tenaga Pendidik MAN 2 Surakarta - Tria Puspita Sari; Wiwik Puspita Dewi; Eko Nugroho; Kania Alfa Anggara; Muthi’ah Nurul Jannah; Ekka Nur Cahyaningrum (TEKIBA : Jurnal Teknologi dan Pengabdian Masyarakat, 2026)
Adolescents face increasingly complex health problems, particularly related to mental health, thus systematic efforts are needed to help them think critically and address the issues they experience. One strategy to improve students’ health status is by optimizing the School Health Efforts (UKS) integrated with the role of accompanying teachers. Madrasah Aliyah 2 Surakarta (MAN 2 Surakarta) is a private Islamic-based school where a situational analysis revealed low access to mental health information and suboptimal management of guidance and counseling services. Data show that around 80–90 students sought counseling in the past year with various problems such as learning motivation, family conflicts, and peer conflicts that required referral to psychiatrists. Although a counseling room facility is available, access to mental health literacy remains limited. Most students have not yet received adequate information on mental health, and teacher training in managing adolescent mental health is also still very limited. The purpose of this community service is to enhance and optimize the roles of School Health Ambassadors (Duta UKS) and educators through the *PEDULI SEJIWA* Program (Center for Self-Education and Mental Literacy for Adolescents with a Healthy Mind and Body) as an effort to improve students’ mental health. This activity is carried out through training, development of educational modules, and improvement of counseling room facilities. The methods applied in this program include situational analysis, socialization, and PEDULI SEJIWA training. The training results showed a 9% increase in knowledge from before (pre-test 91%) to after (post-test 100%).